Multiple regression model for identification of material concentration and color reading. (October 2019) - Zhang, Hanping
Abstract: According to the experimental data, the color dimensions of different concentrations of five substances were analyzed, and reasonable data was selected to analyze the correlation between concentration and color readings. The quantitative relationship model between material concentration and color reading was established by multiple regression. Considering the autocorrelation of the variables, a one-dimensional regression model of concentration and gray scale was established for sulfur dioxide. The two models were tested and were significant with minimal error. This method can be extended to measuring the concentration of the substance In practice.